102k views
4 votes
Pls help
simplify 24x2 − 52x + 20

User Seleena
by
4.6k points

2 Answers

2 votes

Answer:

(3x - 1) • (2x + 5)

Explanation:

Pull out like factors :

24x2 + 52x - 20 = 4 • (6x2 + 13x - 5)

Trying to factor by splitting the middle term

Factoring 6x2 + 13x - 5

The first term is, 6x2 its coefficient is 6 .

The middle term is, +13x its coefficient is 13 .

The last term, "the constant", is -5

Step-1 : Multiply the coefficient of the first term by the constant 6 • -5 = -30

Step-2 : Find two factors of -30 whose sum equals the coefficient of the middle term, which is 13 .

-30 + 1 = -29

-15 + 2 = -13

-10 + 3 = -7

-6 + 5 = -1

-5 + 6 = 1

-3 + 10 = 7

-2 + 15 = 13 That's it

Step-3 : Rewrite the polynomial splitting the middle term using the two factors found in step 2 above, -2 and 15

6x2 - 2x + 15x - 5

Step-4 : Add up the first 2 terms, pulling out like factors :

2x • (3x-1)

Add up the last 2 terms, pulling out common factors :

5 • (3x-1)

Step-5 : Add up the four terms of step 4 :

(2x+5) • (3x-1)

User Galdor
by
4.9k points
1 vote

Explanation:


24x^(2) - 52x + 20

Factoring this quadratic gives us the following:


(8x - 4)(3x - 5)